Investigating the impact of imperfections around a wellbore on liner deformation during hydraulic fracturing - Han, Yanhui; Phan, Dung; Abousleiman, Younane; Ruwaili, Khalid (Frontiers in Mechanical Engineering, 2025)
It is essential to maintain the integrity of liner–cement–formation in the well completion and production stages. However, large liner deformations have been extensively experienced during hydraulic fracturing operations in carbonate formations. This work reveals that local collapse and burst may cause the liner to deform during hydraulic fracturing operations. The stressing and deformation of liners are investigated using numerical simulation at two levels. First, a stand-alone liner is compressed from the outside or expanded from the inside to calibrate the plastic parameters by matching the collapse and burst pressures in the liner’s technical specifications. The influence of the non-uniformity of loads and confinement on the liner’s bearing capacity is then investigated. Second, the influence of imperfections in the cement or cavities in the formation on liner deformation in a liner–cement–formation system is explored. Simulation results indicate that the hydraulic communication between the cavities, vugs, or other imperfections in formation or cementing around a liner and hydraulic fractures can introduce an uneven load on the liner, subsequently threatening the integrity of the liner–cement–formation system and causing a large deformation in the liner. This mechanism has not received much attention in the practical hydraulic fracturing operation design.